ESTUDIO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA AGENCIA DE LA COOPERATIVA DE AHORRO Y CRÉDITO PADRE JULIÁN LORENTE LTDA. EN LA CIUDAD DE CELICA - Ávila Jiménez, Karla Nadegda (2019)
The general objective of this thesis project is to determine the feasibility study for the implementation of an agency of the cooperativa de ahorro y crédito Padre Julián Lorente Ltda., in the city of Celica, whose purpose is to offer the best financial services with security and confidence, to improve the labor and productive activities of the sector and thereby raise the quality of life of the population. For the execution of the investigation the deductive, inductive and statistical method was used and between the techniques the bibliography was used, the direct observation and the same survey that helped to compile the different opinions, attitudes and acceptance of the products and financial services on the part of the population. In addition, a sample of 365 people representing the Economically Active Population (EAP) of Celica was taken, who will be subjects of study. As for the results obtained through the market study, the unsatisfied supply and demand of the city was determined, as well as the reception of the agency and the design of the marketing strategies to be used in the execution of the same. In relation to the technical study it was considered that the facilities will be located in the center of the city considering all the requirements and necessary assurances for the good operation, with the objective to offer a good attention to the partners and clients. Regarding the administrative study, the internal and external regulations were established by which the agency will be governed, as well as the structural organization chart and the functions manual according to each job position; in the economic-financial study the investment, income, expenses, profitability and cash flow were estimated to later use the financial evaluation tools, where satisfactory results were obtained and from the financial point of view it is feasible to open the agency of the Savings and Credit Cooperative Padre Julián Lorente Ltda. in the city of Celica.